Sistem Pendukung Keputusan Penentuan Prioritas Utama Pengadaan Stok Barang Menggunakan Metode WASPAS (Studi Kasus : Pondok Roso Pool & Resto ) - Fera Tri Wulandari (JITU : Journal Informatic Technology And Communication, 2023)
Pondok Roso Pool & Resto puts all the items in the warehouse and records the entry and exit transactions. The stock system that runs on Pondok Roso Pool & Resto has a problem in the procurement process. The process of procuring goods at the agency is not only based on the final stock, but also assesses the purchase price of the supplier for each item and assesses whether the item is sold or not to visitors. This of course makes it difficult for management to determine the procurement of stock of goods because of these factors. Errors in the procurement of goods of course result in losses if the goods that have been purchased apparently can’t sell well. There is a solution, namely by designing a decision support system for procurement of stock using the WASPAS method. Simple additive weight method is a weighted sum method that can provide predictions for decision making based on data. The author uses this method because based on several studies can determine the results and ranking of the problems encountered. The system that will be designed by the author can help the agency in determining the ranking of each item to be procured in stock, so that at least be able to help management in making decisions about the items to be purchased.